The Effect of Parenting, Teacher’s Role, and Peers on Children’s Personal Safety Skills in Tangerang - Hasanah, Aswatun; Rahayu, Sri Ratna; Kuswardinah, Asih (Public Health Perspective Journal, 2019)
Indonesia is a country that is experiencing the growth of the occupation where a third of the population of Indonesia is a school age child who is the forerunner of the nation that must be protected. In contrast to the situation almost every day is heard of violence in children who are dominated by sexual violence. In 2010-2017 cases of child violence reached 21 million cases, 42%-58% was a case of sexual violence. The case of child violence increases annually because the child is always positioned as a weak figure. The purpose of this research is to analyze the effect of parenting, teacherÃ¢â‚¬â„¢s role and peers on personal safety skills in Tangerang. This research is a quantitative research, with a cross sectional approach. Research samples amounted to 294 respondents with simple random sampling techniques. The instrument used a questionnaire sheet. The technique of the data collection was done by interviews. The data analysis of this research using Chi-Square and logistic regression. The results of the Chi-Square test were obtained from the parenting (P = 0,039); teacherÃ¢â‚¬â„¢s role (P = 0,021); peers role (p = 0,021). The logistic regression test found results contained in the parenting variables (p = 0,007) and OR 1.394; teacherÃ¢â‚¬â„¢s role (P = 0,000) and OR 6.091; peers role (p = 0.001) and OR 2.260. Personal safety skills are an early effort done in dealing with child sexual abuse. With this skill the child is expected to be responsible for keeping the personal body from sexual offenders.Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â  Ã‚Â